A Plant-Based Dietary Supplement Exhibits Significant Effects on Markers of Oxidative Stress, Inflammation, and Immune Response in Subjects Recovering from Respiratory Viral Infection: A Randomized, Double-Blind Clinical Study Using Vitamin C as a Positive Control - Fink, Bruno; Hunter, John M.; Pietrzkowski, Zbigniew; Fink, Richard; Brunssen, Coy; Morawietz, Henning; Nemzer, Boris (International journal of molecular sciences, 2025)
Respiratory viruses continue to present serious health challenges to human wellness. Growing evidence suggests that the more severe and damaging effects and symptoms of influenza, rhinovirus (RV), respiratory syncytial virus (RSV), and COVID-19 may primarily result from their common ability to disorganize the body’s healthy immune response. The simultaneous over-stimulation of several reactive oxygen species (ROS) pathways and concurrent suppression of bioavailable Nitic Oxide (NO) contribute to an immune disbalance that can lead to cellular oxidative distress and an excessive inflammatory response. This study evaluated the real-time, acute ability of a single, orally administered 50 mg encapsulated dose of a plant-based dietary supplement (“PB-Blend”), compared to 1000 mg of Vitamin C as a positive control, to modulate multiple ROS associated with a dampened immune response, as well as NO and other markers of inflammation, in a cohort recovering from a moderate course of COVID-19. This randomized, double-blind study was performed on 28 individuals 18–24 days after a moderate COVID-19 infection. Participants were orally supplemented with a single encapsulated dose of either 50 mg of PB-Blend or 1000 mg Vitamin C as a positive control. Changes in the levels of bioavailable NO (measured as circulating NOHb) were assessed, as well as the ex vivo cellular formation of mitochondrial, NOX2-, iNOS-, and TNFα-dependent ROS. All parameters were measured in real time before ingestion (baseline), and then at 30, 60, 120, and 180 min after administration. ROS were measured using a portable electron paramagnetic resonance (EPR) spectrometer. Inflammatory, immunity (hsCRP and TNFα plasma levels), interleukin (IL1, IL6, IL8, and IL10), cytokine (IFNγ, TNFα, and NF-κB), and immunoglobulin (IgA, IgM, IgG, and IgE) profiles were also followed. In addition to laboratory and cell function investigations, we performed clinical cardio ergometry, blood O2 saturation, and respirometry examinations. As hypothesized, the collected baseline data from this study group confirmed that mitochondrial, NOX2, and iNOS enzymatic systems were strongly involved in the generation of ROS at 18–24 days following a positive COVID-19 PCR test. Acute single-dose supplementation of 50 mg PB-Blend had a multifunctional impact on ROS and significantly inhibited the following: (a.) mitochondrial ROS levels by up to 56%; (b.) iNOS by up to 60%; and (c.) NOX2-dependent ROS generation by up to 49%. Moreover, 1000 mg Vitamin C supplementation exhibited narrower ROS-mitigating activity by solely inhibiting NOX2-dependent ROS generation by 45%. Circulating NOHb levels were significantly increased after PB-Blend administration (33%), but not after Vitamin C administration. PB-Blend and Vitamin C exhibited similar potential to reduce ex vivo high dose TNFα (200 ng/mL)-induced H2O2 formation. These results suggest that 50 mg of PB-Blend has the potential to modulate disbalanced mitochondria, iNOS, and NOX2 enzymatic systems that can be engendered during respiratory viral infection and subsequent recovery. Moreover, PB-Blend, but not Vitamin C, showed potential to upregulate bioavailable NO, which is known to decline under these conditions. Based upon these observations, PB-Blend could be considered an alternative to, or to be used in tandem with Vitamin C in applications that promote immune support and recovery during seasons of heightened respiratory viral risk (e.g., “flu season”).